Assessment of arterial hypervascularity of hepatocellular carcinoma: comparison of contrast-enhanced US and gadoxetate disodium-enhanced MR imaging. - Sugimoto K; Moriyasu F; Shiraishi J; Saito K; Taira J; Saguchi T; Imai Y; Sugimoto, Katsutoshi; Moriyasu, Fuminori; Shiraishi, Junji; Saito, Kazuhiro; Taira, Junichi; et al. (European Radiology, 2012)
Objective: To compare contrast-enhanced (CE) ultrasound with gadoxetate disodium-enhanced magnetic resonance (MR) imaging in the assessment of arterial hypervascularity of hepatocellular carcinoma (HCC) and dysplastic nodule (DN), with CT during hepatic arteriography (CTHA) as the reference standard.Methods: This study included 54 consecutively diagnosed patients, with 57 histologically confirmed HCCs and 3 DNs (high-grade). All patients underwent CE ultrasound, gadoxetate disodium-enhanced MR imaging and CTHA. Two trained diagnostic radiologists interpreted the CTHA images and rated the degree of intratumoral arterial vascularity by consensus using a five-point confidence scale as the reference standard. In the observer study, the degrees of vascularity on CE ultrasound and gadoxetate disodium-enhanced MR images were qualitatively analysed by four independent readers using a five-point confidence scale. Diagnostic accuracy was analysed by receiver-operating characteristic (ROC) analysis.Results: The diagnostic accuracies of the average area under the ROC curve (AUC) were significantly greater with CE ultrasound (average AUC: 0.94; 95% confidence interval [CI]: 0.88-1.00) than with gadoxetate disodium-enhanced MR imaging (average AUC 0.84, 95% CI 0.74-0.93, P = 0.0014).Conclusion: Contrast-enhanced ultrasound yields a significantly higher AUC value than gadoxetate disodium-enhanced MR imaging in the assessment of arterial hypervascularity of HCC and DN.Key Points: • Arterial hypervascularity is an important feature determining treatment options in hepatocellular carcinoma. • It can be assessed by contrast-enhanced (CE) ultrasound or magnetic resonance (MR) imaging. • CE ultrasound was more accurate than Gd-EOB-DTPA MRI in assessing intratumoral vascularity. • Hypovascular hepatic nodules should be further investigated using CE ultrasound.